Changes in Vitreoretinal Adhesion With Age and Region in Human and Sheep Eyes - Creveling, Christopher J.; Colter, Jourdan; Coats, Brittany (Frontiers in Bioengineering and Biotechnology, 2018)
While several studies have qualitatively investigated age- and region-dependent adhesion between the vitreous and retina, no studies have directly measured the vitreoretinal strength of adhesion. In this study, we developed a rotational peel device and associated methodology to measure the maximum and steady-state peel forces between the vitreous and the retina. Vitreoretinal adhesion in the equator and posterior pole was measured in human eyes from donors ranging 30 to 79 years of age, and in sheep eyes from premature, neonatal, young lamb, and young adult sheep. In human eyes, maximum peel force in the equator (7.24±4.13 mN) was greater than in the posterior pole (4.08±2.03 mN). This trend was especially evident for younger eyes from donors 30 to 39 years of age. After 60 years of age, there was a significant decrease in the maximum equatorial (4.69±2.52 mN, p=0.016) and posterior pole adhesion (2.95±1.25 mN, p=0.037). In immature sheep eyes, maximum adhesion was 7.60±3.06 mN, and did not significantly differ between the equator and posterior pole until young adulthood. At this age, the maximum adhesion in the equator nearly doubled (16.67±7.45 mN) that of the posterior pole, similar to the young adult human eyes. Light microscopy images suggest more disruption of the inner limiting membrane (ILM) in immature sheep eyes compared to adult sheep eyes. Interestingly, in human eyes, ILM disruption was significantly greater in the posterior pole (p<0.05) and in people over 60 years of age (p<0.02). These findings supplement the current discussion surrounding age-related posterior vitreous detachment, and the risk factors and physiological progressions associated with this condition. In addition, these data further our understanding of the biomechanical mechanisms of vitreoretinal adhesion, and can be used to develop age-appropriate computational models simulating retinal detachment, hemorrhaging or retinal trauma.